A review of techniques for simultaneous enhancement of evaporation and condensation rates in solar stills. (1st September 2021) - Shoeibi, Shahin; Rahbar, Nader; Abedini Esfahlani, Ahad; Kargarsharifabad, Hadi
Abstract: Over the recent years, a great deal of research has been conducted on various parameters of solar stills owing to their low cost of water production rate and feasibility of use in the most types of climate and being environmentally friendly. The water production rate and thermal efficiency of a solar still is mostly affected by the temperature difference between water and glass cover. Various designs have been proposed for the components of solar stills, including geometry, water depth, insulation thickness, and glass thickness and other designs have been coupled with some methods to increase the water temperature and reduce the glass temperature. Simultaneous use of these methods increases the temperature difference between evaporation and condensation areas and results in an increase in the water production rate. The present review paper aimed to evaluate the effect of simultaneous use of different methods to improve the performance of a solar still. For this purpose, some methods for increasing water temperature, such as nanoparticles, PCM, thermoelectric heating, photovoltaic/thermal, solar collector, air heater, and electrical heater and other methods to decrease temperature of condensation area, including the glass cooling, external condenser, and thermoelectric cooling were studied. Future research on hybrid techniques on solar stills is also added in this review paper. The results showed that the highest increased water productivity was obtained in a solar still with water glass cooling and PV/T, which were about 6 times higher than the conventional solar still. Moreover, the lowest CPL is belonged to a solar still with external condenser, PCM, wick material, which was about 0.011/L.